2022
DOI: 10.1177/21582440221085257
|View full text |Cite
|
Sign up to set email alerts
|

When Self-Sacrificial Leaders Induce Employees’ Citizenship Behaviors? Uncovering the Nexus of Psychological Empowerment and Psychological Well-Being

Abstract: The main objective of this study is to examine the effect of self-sacrificial leadership on organizational citizenship behavior within the health sector through a moderated mediation approach. The study has been conducted on nurses working in public hospitals in Sargodha, Pakistan, and data have been collected through a questionnaire survey method. In this study, psychological empowerment is used as a moderator, and psychological wellbeing is used as a mediator between self-sacrificial leadership on organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…In this study, the COVID-19 pandemic was used as a backdrop to examine SSL in dealing with nurses’ WWB and WFC caused by this pandemic. The findings suggest that SSL significantly increased nurses’ WWB and mitigated their WFCs during the COVID-19 crisis (Hypothesis 1), which is consistent with the findings that SSL significantly determines nurses’ well-being (Iqbal et al, 2022) and such leadership may be effective in responding adequately to crises. Also, our research advances the literature on SSL in external crises.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In this study, the COVID-19 pandemic was used as a backdrop to examine SSL in dealing with nurses’ WWB and WFC caused by this pandemic. The findings suggest that SSL significantly increased nurses’ WWB and mitigated their WFCs during the COVID-19 crisis (Hypothesis 1), which is consistent with the findings that SSL significantly determines nurses’ well-being (Iqbal et al, 2022) and such leadership may be effective in responding adequately to crises. Also, our research advances the literature on SSL in external crises.…”
Section: Discussionsupporting
confidence: 81%
“…When faced with demanding work tasks, they were less sensitive to external factors; instead, more personal internal resources preferentially stimulated their internal motivation and thus drove their behavior (Kotzé, 2021). In contrast, SSL represents an environmental factor, an external resource more closely associated with employees’ external motivation (Iqbal et al, 2022). In addition, two dimensions of TAW—learning and vitality—are temporary internal attributes that manifest a positive emotional state within the individual (Spreitzer et al, 2005; Spreitzer & Porath, 2014; Walumbwa et al, 2018), making them more sensitive to intrinsic motivation.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…In conclusion, organizations that implement psychological empowerment programs are well-positioned to enhance OCBs and reduce intentions of employee turnover and retention [31]. Empowerment serves as a catalyst for motivating employees to exert their optimal eforts and signifes a heightened organizational commitment to goal achievement [32].…”
Section: Psychological Empowerment and Ocbsmentioning
confidence: 99%
“…Studies have indirectly shown that well-being can increase positive behaviour in the workplace (Iqbal et al, 2022). Also included in this positive condition is the absence of work stress or burnout (see also Iqbal et al, 2022)…”
Section: Sustainable Well-being Affects Job Embeddedmentioning
confidence: 99%